Empowerment and social inclusion through Para sports: a qualitative study on women with physical impairments in Saudi Arabia - Alhumaid, Majed M.; Adnan, Yuhanis; Said, Mohamed A.; Alobaid, Maryam A.; Khoo, Selina (Frontiers in Psychology, 2024)
Background: Participation in sports represents a potent means of empowerment and social inclusion. Nevertheless, women with physical impairments encounter specific challenges in accessing Para sports. The main aim of this study is to present the experiential participation and achievements in sports of women with physical impairments in Saudi Arabia. Methods: Twenty women athletes with physical impairments who engaged in competitive Para sports in Saudi Arabia were interviewed. Interpretive phenomenological analysis was employed to extract themes elucidating the experiences of women athletes with physical impairments in Para sports. Results: Four dimensions were identified: (i) Exploring participation in sports; (ii) The positive impact of participation in sports; (iii) obstacles in participation in sport; and (iv) hopes and aspirations to improve participation in Para sports. Conclusions: In Saudi Arabia, participation in Para sports functions as a powerful tool for empowering and socially integrating women with physical impairments. However, these women encounter challenges in accessing sports. Achieving empowerment in Para sports necessitates the establishment of an inclusive ecosystem that celebrates diversity and equality. Collaborative efforts from governments, sports organizations, communities, and individuals are indispensable in creating an environment where women with impairments can flourish in sports.